Oil Price and Stock Market: Empirical Evidence from Nigeria - Akinlo, Olayinka Olufisayo (European Journal of Sustainable Development, 2014)
<!--[if gte mso 9]> <![endif]--> This paper examined the relationship between changes in oil prices and stock market growth over the period 1981-2011 using vector error correction modeling approach. The results suggest a long run relationship between oil price, exchange rate and stock market growth. A unidirectional causality runs from oil price change to stock market development. The impulse response function shows that oil price has a temporary positive impact on stock market. The VDC shows that stock market development to be very much dependent on shock on oil price change. Keywords: oil price, stock market, VECM, Nigeria <!--[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->